BEBERAPA KAEDAH MEMAHAMI MAKSUD SYARIâAH - Ilham, Ilham (Al AHKAM: Jurnal Kajian Ilmu Hukum dan Syariah, 2012)
Developmental problems over time faced by humanity are not necessarily the answer can be found in the Quran and Sunnah based on the understanding of human beings in general, but requires a study of the experts, because the Quran and Sunnah composed in Arabic , and people who have the ability to understand the rules of the Arabic language, which could give an explanation. Ijtihad is therefore needed by the mujtahid. In this paper will be presented the steps taken in Understanding the meaning of shariah is holding on lafadz zahir, meaning lafadz and the zahir and meaning lafadz